Literature Review: The Impact of Nutrition and Health on the Process of Growth and Development of Children - Husna, Annisa Ul (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2024)
Children's health and nutrition become critical in human growth and development. This abstract reviews the literature on the effects of nutrition and child health, highlighting the importance of balanced nutrition in supporting physical and cognitive development. The correlation of nutritional patterns, children's health status, and their impact on the immune system and immune system is in focus. Cultural and socioeconomic environmental impacts, including the role of parents, are investigated to present a holistic picture. The literature review approach was used with an analysis of key findings, including the role of nutrients such as proteins, vitamins, and minerals. Research highlights malnutrition on child development and its long-term impact. Cultural and environmental factors, as well as nutrition intervention programs in various global contexts, are in the spotlight. Parental involvement, especially education and family support, is also highlighted as a determining factor in forming an environment that supports children's growth and development. Although research is overwhelming, there are still knowledge gaps, such as micronutrient deficiencies and the influence of modern lifestyle changes, that need to be filled. It is hoped that this literature review will contribute to the development of effective and sustainable intervention strategies, forming a community concerned about children's health.